Seroprevalence of syphilis in human immunodeficiency virus patients - Lakshmi, N.; Prasanthi, K.; Kamala, P.; Kalyani, C. Siva; Rao, P. Appa; Gowtham, B. (International Journal of Research in Medical Sciences, 2019)
Background: Syphilis is a sexually transmitted infection caused by, Treponema pallidum. Syphilis facilitates the transmission and acquisition of human immunodeficiency virus (HIV) and causes transient increase in the viral load. Sexually transmitted infections (STI) are 3-5 times more likely to acquire HIV infection, if exposed to the virus through sexual contact. Aim of the study was to estimate the seroprevalence of Syphilis in HIV patients. Methods: A total of 920 blood samples were collected from HIV patients attending ART (Antiretroviral therapy) centre and were tested for Syphilis by using Rapid Plasma Reagin (RPR) and Treponema pallidum Hemagglutination Assay (TPHA). A total of 100 HIV non-reactive individuals were taken as a control group. Results: Out of 920 samples, 102 (11.1%) were positive for Syphilis. Out of 102 Syphilis seropositive patients, males (76.5%) were more commonly affected in age group of 21-40 years. Both RPR and TPHA were reactive in 46% of cases and only TPHA reactive in 53.9% of cases. Out of 100 HIV non-reactive patients, 5% of patients are reactive for Syphilis. Conclusions: In the present study, prevalence of Syphilis was more in HIV patients compared to HIV non-reactive persons. Persons with HIV infection acquired through sexual route should be screened for Syphilis by one nonspecific test along with specific test to confirm the diagnosis. This will help in proper management of the patients having Syphilis and HIV co-infection.